Comparison of Efficacy of Sublingual vs Rectal Misoprostol in the Prevention of Primary Postpartum Hemorrhage - Attayaba Khan; Rabia Mohsin; Mehnaz Khakwani; Nabila Tariq; Ayema Shabbir; Iqbal, Muhammad (Medical Journal of South Punjab, 2024)
Objective: To determine the efficacy of sublingual vs rectal misoprostol in the prevention of primary postpartum hemorrhage Study Design: Prospective randomized clinical trial Place and Duration: Gynecology Department, Combined Military Hospital Multan for duration of 6 months Methodology: The study was conducted on 200 female pregnant patients, reported in gynecology department of CMH Multan. Divided into two groups, A and B by lottery method with 100 respondents in each group. This study was conducted during Feb 2022 - July 2023. Misoprostol was given at the end of SVD or caesarean. Group A received 4 tablets in 200mcg Misoprostol in sublingual form, while group B received 4 tablets 200 mcg Misoprostol in rectal form. Total blood loss was recorded at the end of surgery with the help of soaked pads. Data was collected, entered and analyzed in SPSS version 26.0 Results: Mean age of respondents in group A was 25.4±4.3 years with gestational age 37.2± 0.90 weeks and in group B it was 26.2± 4.6 years with gestational age 37.9±1.0 weeks. Mean blood loss in Group was 541±123ml in relation to Group B where mean blood loss was 401±96ml. In group A 30 (30%) while in group B 15(15%) participants suffered from postpartum hemorrhage. Postpartum hemorrhage was considerably lower in Group-B compared to Group-A women and found statistically significant (p-value<0.001). Conclusion: Misoprostol is effective in reducing bleeding though rectal misoprostol was found better than the sublingual technique for hemorrhage control.